Model Keluarga Hafizh di Era Digital (Kajian Atas Buku Rahasia Sukses 3 Hafizh Qur’an Cilik Mengguncang Dunia) - Rosdianti, Meti Sari; Ritonga, Apri Wardana; Khalilah Ramadhani; Mila Nurrohmah; Mumfangati (Indonesia Islamic Education Journal, 2023)
We still encounter the crisis of the generation of Qur’an memorizers and illiterates in Indonesia, where in fact the majority are Muslims. The family has an important role in creating a generation of memorizers of the Qur'an. Methods of memorizing the Al-Qur'an are now starting to develop, various methods have emerged to make it easier for memorizers of the Al-Qur'an, both for toddlers, teenagers and adults. By using a method, it can memorize more easily, effectively, and have a good level of memorization power. The purpose of this research is to describe the key to the success of the parents of Tabarok, Yazid and Zeenah in bringing their three children to become young hafizh of the Qur'an and the Tabarak family method has successfully led three siblings to become the youngest hafizh in the world. This study uses a qualitative research design with the library research method, namely research that utilizes library materials as data sources. This research method aims to provide an overview of the hafidz family model in the digital era based on a study of the book entitled "Rahasia Sukses 3 Hafidz Qur’an cilik Mengguncang Dunia". This study found a method of memorizing the Qur'an (tabarak method), namely, the talqin method repeated up to 20 times each day. After mentalqin, listen to the recitation of the verse from CD recordings of famous reciters.